Linguistic Impoliteness and Power Relations In AlRawabi School For Girls: An Analysis Based On Culpeper’s Theory: Al-Waqahah al-Lughawiyyah wa ‘Alaqat al-Quwwah fi Madrasat al-Rawabi lil-Banat: Tahlil fi Daw’i Nazariyyat Culpeper - Alifa Maisya Ratunisa (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study examines linguistic impoliteness strategies in the Netflix series AlRawabi School for Girls based on Jonathan Culpeper's impoliteness theory using a descriptive qualitative approach within a pragmatic framework. Data were collected from verbal utterances across all six episodes using official Netflix subtitles and resulted in 27 impolite utterances identified for analysis. Among the identified strategies, positive impoliteness was the most dominant strategy with 12 utterances (44%), followed by bald on record impoliteness with 10 utterances (37%), negative impoliteness with 3 utterances (11%), sarcasm or mock politeness and withhold politeness with 1 utterance each (4%). These findings demonstrate that linguistic impoliteness functions not only as an emotional expression but also as a social practice in which characters establish dominance, negotiate power relations, and reinforce social hierarchies. By extending beyond the identification of impoliteness strategies, this study contributes to pragmatic studies of impoliteness by providing a contextual understanding of how linguistic impoliteness operates within an Arab adolescent school setting. تهدف هذه الدراسة إلى استراتيجيات الوقاحة اللغوية في مسلسل